Morphology and molecules reveal the alien Posthodiplostomum centrarchi Hoffman, 1958 as the third species of Posthodiplostomum Dubois, 1936 (Digenea: Diplostomidae) in Europe - Stoyanov, Borislav; Georgieva, Simona; Pankov, Plamen; Kudlai, Olena; Kostadinova, Aneta; Georgiev, Boyko B (Systematic parasitology, 2017)
Metacercariae of two species of Posthodiplostomum Dubois, 1936 (Digenea: Diplostomidae) were subjected to morphological and molecular studies: P. brevicaudatum (von Nordmann, 1832) from Gasterosteus aculeatus (L.) (Gasterosteiformes: Gasterosteidae), Bulgaria (morphology, cox1 and ITS1-5.8S-ITS2) and Perca fluviatilis L. (Perciformes: Percidae), Czech Republic (morphology, cox1, ITS1-5.8S-ITS2 and 28S); and P. centrarchi Hoffman, 1958 from Lepomis gibbosus (L.) (Perciformes: Centrarchidae), Bulgaria (morphology, cox1 and ITS1-5.8S-ITS2) and Slovakia (cox1 and ITS1-5.8S-ITS2). In addition, cercariae of P. cuticola (von Nordmann, 1832) from Planorbis planorbis (L.) (Mollusca: Planorbidae), Lithuania (morphology and cox1) and metacercariae of Ornithodiplostomum scardinii (Schulman in Dubinin, 1952) from Scardinius erythrophthalmus (L.) (Cypriniformes: Cyprinidae), Czech Republic, were examined (morphology, cox1, ITS1-5.8S-ITS2 and 28S). These represent the first molecular data for species of Posthodiplostomum and Ornithodiplostomum Dubois, 1936 from the Palaearctic. Phylogenetic analyses based on cox1 and ITS1-5.8S-ITS2, using O. scardinii as the outgroup and including the three newly-sequenced Posthodiplostomum spp. from Europe and eight published unidentified (presumably species-level) lineages of Posthodiplostomum from Canada confirmed the distinct status of the three European species (contrary to the generally accepted opinion that only P. brevicaudatum and P. cuticola occur in the Palaearctic). The subspecies Posthodiplostomum minimum centrarchi Hoffmann, 1958, originally described from North America, is elevated to the species level as Posthodiplostomum centrarchi Hoffman, 1958. The undescribed "Posthodiplostomum sp. 3" of Locke et al. (2010) from centrarchid fishes in Canada has identical sequences with the European isolates of P. centrarchi and is recognised as belonging to the same species. The latter parasite, occurring in the alien pumpkinseed sunfish Lepomis gibbosus in Europe, is also supposed to be alien for this continent. It is speculated that it colonised Europe long ago and is currently widespread (recorded in Bulgaria, Slovakia and Spain); based on the cox1 sequence of an adult digenean isolate from the Ebro Delta, Spain, only the grey heron (Ardea cinerea L.) (Ciconiiformes: Ardeidae) is known to be its definitive host in Europe.
Keywords: Electron Transport Complex IV; Phylogeny; Evropa; ribozomální DNA; Perciformes; druhová specificita; Europe; DNA, Ribosomal; Animals; Species Specificity; respirační komplex IV; Smegmamorpha; zvířata; fylogeneze; Trematoda